2023
DOI: 10.3350/cmh.2023.0274
|View full text |Cite
|
Sign up to set email alerts
|

Current evidence and the potential role of proton beam therapy for hepatocellular carcinoma

Sung Uk Lee,
Tae Hyun Kim

Abstract: Hepatocellular carcinoma (HCC) is a leading cause of cancer-related death, and external beam radiation therapy has emerged as a promising approach for managing HCC. Proton beam therapy (PBT) offers dosimetric advantages over X-ray therapy, with superior physical properties known as the Bragg peak. PBT holds promise for reducing hepatotoxicity and allowing safe dose-escalation to the tumor. It has been tried in various clinical conditions and has shown promising local tumor control and survival outcomes. A rece… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 66 publications
0
3
0
Order By: Relevance
“…They also mentioned PBT had been used successfully in challenging clinical conditions, such as major vascular invasion and re-irradiation. 12 Recently, the first phase III randomized controlled trial demonstrated that PBT was associated with local progression-free survival rates that were comparable to those observed for thermal ablation in patients with recurrent small (<3 cm) HCC. 14 In addition to aforementioned advantage of particle therapy, CIRT possesses further distinctive attributes.…”
Section: Editorialmentioning
confidence: 90%
See 2 more Smart Citations
“…They also mentioned PBT had been used successfully in challenging clinical conditions, such as major vascular invasion and re-irradiation. 12 Recently, the first phase III randomized controlled trial demonstrated that PBT was associated with local progression-free survival rates that were comparable to those observed for thermal ablation in patients with recurrent small (<3 cm) HCC. 14 In addition to aforementioned advantage of particle therapy, CIRT possesses further distinctive attributes.…”
Section: Editorialmentioning
confidence: 90%
“…Particle therapy that can be used in the management of HCC is mainly divided into proton beam therapy (PBT) and carbon ion RT (CIRT). 11,12 The main physical characteristics of particle therapy is the absorbed dose curve shows a slow initial increase with the penetration through matter, than a steep rise to the maximum, known as the Bragg peak, followed by a sharp fall in energy absorption toward the end of the beam range. 13 This unique characteristics can be able to provide a more precise dose delivery to the tumor, while minimizing radiation effect to the surrounding normal tissues effectively.…”
Section: Editorialmentioning
confidence: 99%
See 1 more Smart Citation